Glucose-6-Phosphate Dehydrogenase Deficiency and Sickle Cell Trait among Prospective Blood Donors: A Cross-Sectional Study in Berekum, Ghana - Patrick Adu; David Larbi Simpong; Godfred Takyi; Richard K. D. Ephraim (Advances in Hematology)
Background. Blood transfusion is a therapeutic procedure usually undertaken in patients with severe anaemia. In Ghana, severe anaemia is mostly due to malaria caused by severe Plasmodium falciparum infection, road traffic accidents, and haemoglobinopathy-induced acute haemolysis. Method. This cross-sectional study evaluated coinheritance of sickle cell haemoglobin variant and G6PD enzymopathy among individuals that donated blood at the Holy Trinity Hospital, Berekum, in the Brong-Ahafo Region, Ghana. Demographic data and other pertinent information were captured using questionnaire. Sickle cell haemoglobin variants were determined using cellulose acetate electrophoresis (pH 8.6). Qualitative G6PD status and quantitative G6PD enzyme activity were determined using methaemoglobin reduction and Trinity Biotech G6PD test kit, respectively. Results. Prevalence of sickle cell trait (SCT) and G6PD enzymopathy coinheritance was 7%. In addition, 19.5% of the donors had 10%–60% of normal G6PD enzyme activity suggesting that these donor units are prone to stressor-induced acute haemolysis when given to recipients. Mild G6PD activity (p=0.03, OR: 2.410 (CI: 1.049–5.534)), commercial (p=0.020, OR: 5.609 (CI: 1.309–24.035)), and voluntary (p=0.034, OR: 2.404 (CI: 1.071–5.397)) donors were significantly associated with SCT. Conclusion. Screening for red cell pathologies must be incorporated into existing protocols for populations with high incidence of haemoglobinopathies to protect high-risk recipients.